2016
DOI: 10.1089/cyber.2015.0359
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Social Networks and Communication Channels in a Web-Based Peer Support Intervention

Abstract: Web and mobile (mHealth) interventions have promise for improving health outcomes, but engagement and attrition may be reducing effect sizes. Because social networks can improve engagement, which is a key mechanism of action, understanding the structure and potential impact of social networks could be key to improving mHealth effects. This study (a) evaluates social network characteristics of four distinct communication channels (discussion board, chat, e-mail, and blog) in a large social networking interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…Participants and facilitators were invited to post messages to the group at any time to solicit feedback, update other members about their current situation, or follow up on activities that were assigned during the weekly chat session. A webmail feature was also included in health-space.net, where participants had the option to email the entire group or only specific participants or facilitators (28). In order to promote group cohesion, participants were also encouraged to create a profile in which they could describe themselves and their experience with cancer and/or share photos.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants and facilitators were invited to post messages to the group at any time to solicit feedback, update other members about their current situation, or follow up on activities that were assigned during the weekly chat session. A webmail feature was also included in health-space.net, where participants had the option to email the entire group or only specific participants or facilitators (28). In order to promote group cohesion, participants were also encouraged to create a profile in which they could describe themselves and their experience with cancer and/or share photos.…”
Section: Methodsmentioning
confidence: 99%
“…Interventions that marry evidence-based approaches from face-to-face interventions with social components that allow interactions between participants may be particularly effective at delivering online content. We have previously demonstrated that engaging with a social-networking community in an online intervention for cancer survivors is associated with a 5-fold increase in interaction with structured intervention elements, such as coping skills-training exercises and psychoeducational content (28). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Another recurring finding is that users may prefer different social media platforms, making formative research and/or use of multiple channels an important consideration. 7,41 …”
Section: Key Principles Of Social Media To Enhance Cancer Prevention mentioning
confidence: 99%
“…Interventions combining more levels of interaction, participation, and integral communication are expected to meet higher needs in a greater number and diversity of patients due to their greater flexibility and adaptability. Encouraging patients to participate is also easier when a professional facilitator is involved in the intervention …”
Section: Resultsmentioning
confidence: 99%